2015
DOI: 10.1007/s10880-015-9436-5
|View full text |Cite
|
Sign up to set email alerts
|

Are Single-Item Global Ratings Useful for Assessing Health Status?

Abstract: The research performance of the single-item self-rating In general, would you say your health is: excellent, very good, good, fair, or poor? was evaluated relative to the SF-36 General Health Scale that contains this item, using data for a sample of psychiatric outpatients who had co-occurring chronic physical conditions (N = 177). The scale was more robust than the single-item in cross-sectional validity tests and for predicting 2-year outcomes, but the single-item had stronger discriminant validity as a meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 77 publications
2
59
0
Order By: Relevance
“…The single-item perceived health status question has been demonstrated to have adequate convergent and discriminant validity, as well as adequate reliability and sensitivity [ 45 ]. In this study, we found that a fair or poor perceived health status was significantly associated with a four-fold increase in the risk of depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The single-item perceived health status question has been demonstrated to have adequate convergent and discriminant validity, as well as adequate reliability and sensitivity [ 45 ]. In this study, we found that a fair or poor perceived health status was significantly associated with a four-fold increase in the risk of depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Health status was assessed using two items of general self-rated health (GSRH), consistent with the approach to measuring self-rated health adopted by DeSalvo et al (2006). Although the wording of single-item measures of health status may vary slightly, they have been found to predict a number of health outcomes on par with or even better than multi-item and multi-factor instruments, including chronic physical conditions (e.g., Macias, Gold, € Ong€ ur, Cohen, & Panch, 2015), quality of life (DeSalvo et al, 2006), mortality (e.g., DeSalvo, Fan, McDonell, & Fihn, 2005), and prospective health expenditure (e.g., DeSalvo et al, 2009). The first item, GSRHstandard (GSRH-S), asked participants to answer a standard question about their health: 'How would you say your health is?'…”
Section: Methodsmentioning
confidence: 99%
“…For narcissism, a single-item measurement was also developed, showing high test-retest-reliability and acceptable validity [37]. Even assessing the health status with global single-items as a valid, reliable, and sensitive measurement can be done [38]. …”
Section: Introductionmentioning
confidence: 99%